Effects of substituting municipal waste incineration fly ash for lime on generating a bonding phase during the sintering process. (1st January 2023) - Jiang, Zhenqiang; Dong, Kai; Wang, Hongyang; Zhou, Yun; Tian, Bohan; Li, Xin; Zhu, Rong
Abstract: As the main solid by-product of municipal waste incineration, the safe treatment and resource utilization of municipal waste incineration fly ash (hereafter referred to as fly ash), comprising a large amount of CaO, SiO2, Al2 O3, and related compounds, has become an exceedingly important environmental concern. Owing to its alkaline composition, herein we propose that fly ash replaces lime as a part of the flux used in the sinter process. Following a combined approach using thermodynamic calculations and experimental verification, we found that CaO from fly ash can combine with Fe2 O3 to form complex calcium ferrite, which can effectively replace lime to form the binder phase for the sintering process. In addition, a small amount of Al2 O3 impurities present in fly ash promotes the formation of acicular calcium ferrite with an interwoven structure, which improves the reducibility and mechanical strength of the sintered ore. However, when the proportion of fly ash replacing lime is too high and results in an Al2 O3 content greater than 2%, the acicular calcium ferrite is transformed to the plate state, which deteriorates the metallurgical properties of the sintered ore. Furthermore, alkaline metal chlorides (e.g., KCl and NaCl) present in fly ash can improve the dissolution of Al2 O3 and SiO2 in silicate, which impedes the performance of the binder phase. However, most of the alkali metal chlorides are volatilized, and only a small amount remains in the form of oxides, which have little effect on the performance of the sintered binder phase. Overall, the best metallurgical properties were obtained when fly ash replaced 25% lime as the sintering alkaline flux. Therefore, replacing lime with fly ash to form the binder phase during sintering holds excellent application prospects. Highlights: The advantages and feasibility of using the sintering process to consume the municipal waste incineration fly ash. The characteristics of fly ash make it have good sintering raw material properties. Thermodynamic Calculation of the Effect of Al2O3 and Alkali Metals in Fly Ash on the Sintering Binder Phase. Thermodynamic Experiment of Fly ash substituting part of Lime as sintering alkaline flux Ratio.